Pediatric Dental Insurance Coverage as an Unmet Demand? - Atefeh Najafi Shahkoohi; Maryam Moeeni (مجله دانشکده دندانپزشکی اصفهان, 2024)
The coverage of dental services by the health system is not only related to reducing the financial burden of oral and dental diseases of households but also helps to improve the oral and dental health of children. The purpose of this study is to investigate the prioritization of parents to cover dental services for children in the form of basic medical insurance.Materials & Methods:The present study is a cross-sectional survey that was conducted in Isfahan City in the winter of 2018 and spring of 2019. The statistical population included households with children aged 6-12 who, at the time of sampling, had visited public and private dental clinics with pediatric dental specialists in Isfahan City to receive dental services for children. Data collection was done through a researcher-made questionnaire. Out of the 464 questionnaires, 51 questionnaires were completed online and 413 questionnaires were completed through face-to-face interviews. STATA 14 software was used for data analysis.Results:The findings of the study show that the expansion of pediatric dental care in social health insurance is a priority for parents.Conclusion:The findings of the study show that the expansion of children's dental services in social health insurance is an unmet demand. This finding can be of interest to oral and dental health policymakers as well as medical insurance policymakers